Morphometric analysis of long-term dentoskeletal effects induced by treatment with Balters bionator - Bigliazzi, Renato [UNESP]; Franchi, Lorenzo; Bertoz, André Pinheiro de Magalhães [UNESP]; McNamara, James A.; Faltin Júnior, Kurt; Bertoz, Francisco Antonio [UNESP] (The Angle Orthodontist (EH Angle Education & Research Foundation), 2014)
Objective: To evaluate the long-term effects of the standard (Class II) Balters bionator in growing patients with Class II malocclusion with mandibular retrusion by using morphometrics (thin-plate spline [TPS] analysis). Materials and Methods: Twenty-three Class II patients (8 male, 15 female) were treated consecutively with the Balters bionator (bionator group). The sample was evaluated at T0, start of treatment; T1, end of bionator therapy; and T2, long-term observation (including fixed appliances). Mean age at the start of treatment was 10 years 2 months (T0); at posttreatment, 12 years 3 months (T1); and at long-term follow-up, 18 years 2 months (T2). The control group consisted of 22 subjects (11 male, 11 female) with untreated Class II malocclusion. Lateral cephalograms were analyzed at the three time points for all groups. TPS analysis evaluated statistical differences (permutation tests) in the craniofacial shape and size between the bionator and control groups. Results: TPS analysis showed that treatment with the bionator is able to produce favorable mandibular shape changes (forward and downward displacement) that contribute significantly to the correction of the Class II dentoskeletal imbalance. These results are maintained at a long-term observation after completion of growth. The control group showed no statistically significant differences in the correction of Class II malocclusion. Conclusions: This study suggests that bionator treatment of Class II malocclusion produces favorable results over the long term with a combination of skeletal and dentoalveolar shape changes.
Keywords: Functional jaw orthopedics; Class II malocclusion; Morphometric analysis; Thin-plate spline analysis